2009
DOI: 10.1101/gr.092353.109
|View full text |Cite
|
Sign up to set email alerts
|

Nucleosomes are well positioned in exons and carry characteristic histone modifications

Abstract: The genomes of higher organisms are packaged in nucleosomes with functional histone modifications. Until now, genomewide nucleosome and histone modification studies have focused on transcription start sites (TSSs) where nucleosomes in RNA polymerase II (RNAPII) occupied genes are well positioned and have histone modifications that are characteristic of expression status. Using public data, we here show that there is a higher nucleosome-positioning signal in internal human exons and that this positioning is ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

45
277
2
4

Year Published

2010
2010
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 289 publications
(331 citation statements)
references
References 52 publications
45
277
2
4
Order By: Relevance
“…Indeed, we observe enrichment for phosphorylated RNAPII at these sites (Supplemental Fig. S11), and the preferential positioning of nucleosomes at exon borders, reminiscent of 59 and 39 gene termini, has been recently reported (Andersson et al 2009;Nahkuri et al 2009;Schwartz et al 2009;Spies et al 2009;Tilgner et al 2009). …”
Section: Discussionmentioning
confidence: 92%
“…Indeed, we observe enrichment for phosphorylated RNAPII at these sites (Supplemental Fig. S11), and the preferential positioning of nucleosomes at exon borders, reminiscent of 59 and 39 gene termini, has been recently reported (Andersson et al 2009;Nahkuri et al 2009;Schwartz et al 2009;Spies et al 2009;Tilgner et al 2009). …”
Section: Discussionmentioning
confidence: 92%
“…Remarkably, the pattern of these alterations was not irregular, raising a question of the underlying mechanism. Apart from alterations of cross-exon protein interactions and/or RNA secondary/tertiary structure, chromatin and histone modifications have been recently shown to influence splicing [Andersson et al, 2009;Gama-Carvalho et al, 1997;Kolasinska-Zwierz et al, 2009;Kornblihtt et al, 2009;Schor et al, 2009;Tilgner et al, 2009]. Exon marking and nucleosome occupancy between exons and introns also show only ~1.5-fold differences and nucleosome occupancy improved exon recognition only to a limited degree [Spies et al, 2009].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the preference of methylation for exons in the various plant and animal species suggests that, like gene body methylation, exon methylation may be an ancestral condition. It has been recently shown that exons are enriched in nucleosome content relative to introns (23)(24)(25), so it is tempting to speculate that nucleosomes might act to guide DNA methyltransferases resulting in higher methylation levels on exons.…”
Section: Danio Rerio Mus Musculusmentioning
confidence: 99%